Implementation of safety-related statutory information for herbal products under the pharmaceutical legislation between 1965 and 2021 in Finland: a content analysis of product information - Sari M. Koski; Anna Hietikko; Marja Airaksinen; Pirjo Laitinen-Parkkonen (Archives of Public Health)
Abstract Background The study aim was to investigate implementation of safety-related statutory information for herbal products under the pharmaceutical legislation between 1965 and 2021 in Finland. The study period covered Finland’s whole marketing authorisation system divided into five periods according to changes in legislation (1965–1982, 1983–1987, 1988–1993, 1994–2004 and 2005–2021). Methods The study was carried out using qualitative content analysis focusing on herbal products granted marketing authorisations, registrations and licenses under the pharmaceutical legislation. Safety-related information in the summaries of product characteristics (SmPC), package leaflets (PL) and their predecessors (i.e., preliminary PLs called brochures) from 1965 to 2021 were analysed, particularly focusing on contraindications – including special warnings and precautions. The herbal product information data were searched from the archives of the Finnish Medicines Agency (Fimea). All searched information was from publicly available EU and Finnish legislations, administrative regulations, and approved product information of SmPC, PL and their predecessors. Results The study material consisted of 207 herbal medicinal products after excluding six products because no data was found for them. Contraindications (including special warnings and precautions) were included in product information more systematically since 2005. Within 1965–1982, only 2/13 (15%) licensed products were equipped with a brochure. During 1994–2004 of the products 64/78 (82%) were equipped with the SmPC, PL or brochure. This legislation period can be seen as a watershed in implementation of SmPC into practice in Finland before the full (100%) implementation during the period 2005–2021. Of the contraindication (including special warnings and precautions) information, hypersensitivity/allergy information was included clearly most frequently. Conclusions This study is based on a unique archive material covering years 1965–2021 in Finland. It shows successful national implementation of statutory product information for herbal products and how safety-related product information on contraindications (including special warnings and precautions) has improved during the study period, particularly since legislative changes in 2005. Currently, all herbal products under pharmaceutical supervision are medicinal products which are controlled like any other medicinal products for patient safety.